A Computational and Experimental Study of a Small-Scale Flat-Shaped Vertical Axis Wind Turbine - Kadir, NF.; Mohamed, H.; Manap, A. (International Journal of Engineering and Technology, 2018)
This paper focuses on a computational and experimental study of flat-shaped turbine blades for a small scale Vertical Axis Wind Turbine (VAWT). In the computational analysis, a 2-Dimensional (2D) wind turbine model with three flat blades was designed using Ansys Flu-ent, which is computational fluid dynamics (CFD) software. The wind speed around the blades was simulated in a range of 3 m/s to 8 m/s. Velocity and pressure distributions of the airflow around the blades were then observed. Pressures acting on the blades surface were then averaged and used to estimate the angular speed of the wind turbine model using the principles of torque and moment of inertia. A small-scale prototype was designed, fabricated and tested to validate the simulation result. Testing results show that the wind turbine prototype can rotate with an average speed of 148.8 rpm when having a 3.27 m/s wind speed. At the similar wind speed, the simulation result has estimated the angular speed to be 119 rpm. The percentage difference of the angular speed is about 20%. . Â Â